Fracture of a multiferroic semicylinder with a magnetoelectroelastic interlayer: Piezoelectric stiffening/softening effects and peak removal of stress intensity factor. (15th June 2016) - Liu, Shi-Lun; Li, Yong-Dong
Highlights: Fracture analysis is made on a multiferroic semi-cylinder with a MEE interlayer. Crack interaction gives rise to local SIF oscillation. Bilateral clamping can remove the upward pulse of SIF-oscillation. PE stiffening always occurs on the PM–MEE interface. PE softening invariably appears on the PE–MEE interface. Abstract: Crack interaction may give rise to local upward pulse of fracture parameter, which is harmful to structural safety. The method to be adopted to remove such pulse is significant but remains unclear. In addition, piezoelectric (PE) stiffening exists in multiferroic composites, but does its counterpart, PE softening, also exist? If yes, when do they occur? These problems deserve study. In the present article, a fracture analysis is performed on a multiferroic semicylinder consisting of a PE inner layer, a magnetoelectroelastic (MEE) interlayer, and a piezomagnetic (PM) outer one. This is the first study to consider the MEE interlayer in multiferroic composites. The combined methods of Green's functions, dislocation simulation, and Cauchy singular integral equations are used for solving the problem. Numerical results are provided for parametric studies, yielding two main conclusions: (a) bilateral clamping is an effective way for removing the upward pulse of the local SIF oscillation induced by crack interaction. (b) Besides the conventional PE stiffening effect, its counterpart effect of PE softening is also noted, both of which depend on the piling way of the PM, PE, and MEE layers. Specifically, PE stiffening always occurs on the PM–MEE interface, while PE softening invariably appears on the PE–MEE interface. Graphical abstract: